Comparison Analysis of Nearest Road Calculations on Dijkstra Algorithm and A*(A-Star) Algorithm for Mapping BTS Tower Area - Hidayat, Agung Rahmad; Gernowo, Rahmat; Sugiharto, Aris (Journal of Social Research, 2023)
BTS (Base Transceiver Station) is a telecommunications infrastructure in the form of a tower with a transmitting antenna that facilitates wireless communication between communication devices and operator networks. BTS as a signal receiver and transmitter, its existence must be known to a user, such as maintenance staff and BTS tower operation staff to deal with existing problems. So a special system is needed for users to use in determining the closest path between the user and the location of the BTS tower. The purpose of this study is to make it easier for the user to determine the shortest path to the intended BTS tower location and to analyze the Dijkstra algorithm and the A* algorithm in determining the shortest route between the user's location and the location of the Telkomsel BTS tower in Semarang, Central Java. The results obtained from the 82 test data tested with the information system created show that Dijkstra's algorithm is more efficient than the A* algorithm. Validation is carried out by calculating with the system between the user's location and 82 test data or the location of BTS towers in the city of Semarang. The results of the validation carried out explained that the system was running according to the functions made and the results of the calculations carried out by the system were appropriate.